Experimental evaluation of damage state and failure propagation of infilled frames under the opening effect - Hsunandar Htun; Khin Su Su Htwe (Researcher and Lecturer Society, 2024)
In this study, four frame specimens were tested: two with concentric window and door openings in the infills, and two with eccentric window and door openings. The serviceability limit of the infilled state was determined by evaluating the structural behaviour of infilled reinforced concrete frames with openings. The results indicate that frames with centrally located openings exhibit a reduction in lateral load capacity. The damage characteristics are influenced more by the location of the opening than by its percentage. When the opening is positioned closer to the edge of the masonry panel, the structural performance improves. Initial cracking occurs at a lateral drift of 0.2%, while crushing of the masonry panel occurs at approximately 2%. In frames with centrally located openings, the segment near the loaded column is more prone to damage, whereas the segment farther from the loaded column shows increased vulnerability.